Development of Brain Based Intervention Model for Learning Acceleration of Children at Early Elementary Level - Fatima, Hafiza Gulnaz; Quraishi, Uzma; Khanam, Afifa (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to develop a brain based intervention model for the learning acceleration of children at early elementary level. A counter balance experimental design was adopted for the study. Total 180 6th graders were selected from 3 different schools, N=60 from each school, taking all elementary school students of Province Punjab as the population of the study. The schools were randomly selected from three areas; urban, suburban and rural areas. In each school, 60 students were distributed in two equal groups of 30 each. The experimental group in each school was taught using three types of activities (cooperative Learning, Practical Simulation, and Problem solving separately) and the control group of thirty students were taught with conventional method. After three months, all experimental groups were given alternative treatments. Another session of three months was taken with the three type of activities alternatively. Cumulatively each experimental group was taught with each strategy but with different sequence. All sessions were pre and post tested including three control groups. The activities were developed from the twelve chapters of General science book of grade 6. Total period of experiment was nine months consisting of three phases of three months. The study found positive affect of cooperative learning, practical simulation and problem solving on students’ academic achievement. The study has implications for the use of brain based acceleration strategies to enhance early elementary students learning.